Case Report: An Atypical Form of Familial Partial Lipodystrophy Type 2 Due to Mutation in the Rod Domain of Lamin A/C - Cecchetti, Carolina; D’Apice, M. Rosaria; Morini, Elena; Novelli, Giuseppe; Pizzi, Carmine; Pagotto, Uberto; Gambineri, Alessandra (Frontiers in Endocrinology, 2021)
Purpose. Familial partial lipodystrophy type 2 (FPLD2) patients generally develop a wide variety of severe metabolic complications. However, they are not usually affected by primary cardiomyopathy and conduction system disturbances, although a few cases of FPLD2 and cardiomyopathy have been reported in the literature. These were all due to amino-terminal heterozygous lamin A/C mutations, which are considered as new forms of overlapping syndromes. Methods and Results. Here we report the identification of a female patient with FPLD2 due to a heterozygous missense variant c.604G>A in the exon 3 of the LMNA gene, leading to amino acid substitution (p.Glu202Lys) in the central alpha-helical rod domain of lamin A/C with a high propensity to form coiled-coil dimers. The patient’s cardiac evaluations that followed the genetic diagnosis revealed cardiac rhythm disturbances which were promptly treated pharmacologically. Conclusions. This report supports the idea that there are “atypical forms” of FPLD2 with cardiomyopathy, especially when a pathogenic variant affects the lamin A/C head or alpha-helical rod domain. It also highlights how increased understanding of the genotype-phenotype correlation could help clinicians to schedule personalized monitoring of the lipodystrophic patient, in order to prevent uncommon but possible devastating manifestations, including arrhythmias and sudden death.